The Law Of Exchanging Pulsa Into Money Using The Ibn Hazm Perspective Rate System (Case Study On Twitter Social Media Users In Medan City) - Lelya Hilda Amira Ritonga; Fatimah Zahara (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Convert or conversion in Indonesian means changing. This means that the service for converting credit to electronic money using a rate or exchange rate system means changing or exchanging credit for money using a rate system that has been determined and mutually agreed between the provider and the recipient of the credit to money conversion service. The results from converting credit into money are more often in the form of electronic money (e-money) than cash because in practice this transaction is more often carried out online on social media. The large number of people who use the service of converting credit to electronic money using a rate system has attracted the attention of the author to study this topic more deeply and also to find out how Islamic law views the practice of using services to convert credit to electronic money. The data sources used are primary and secondary data sources. The author uses field research techniques, interviews and documentation. The case study was conducted on social media Twitter (now X) in Medan City. The conclusion that the author can draw from using the service to convert credit to electronic money with a rate or exchange rate system is as follows: Those who have a lot of credit can convert it into money which can be reused as a transaction tool in buying and selling or other muamalah activities. The view of Islamic law regarding the use of credit conversion services into electronic money with a rate system is in accordance with Islamic provisions and sharia. Credit conversion services are permissible as long as there are no elements that make them haram.